Customer Engagement Transformation: A Critical Factor for Successful Digital Transformation Strategies in the Transportation Industry - Rian Bimo Ankhal; Muharman Lubis; Hanif Fakhrurroja (SENTRI: Jurnal Riset Ilmiah, 2026)
Customer engagement transformation is a key aspect in developing digital transformation strategies in today's workplace. This paper aims to present an analysis of critical success factors (CSFs) that influence customer engagement transformation within the context of digital transformation strategies. The research methodology involves a combination of in-depth case studies of several organizations that have successfully implemented digital transformation strategies with a focus on employee engagement. Customer surveys, interviews with organizational leaders, and internal document analysis are the primary instruments for data collection. This paper will discuss the implications of using the latest technology, digital collaboration platforms, and supportive leadership approaches in achieving customer engagement transformation. We will also explore the impact of factors such as work-life balance, skills development, and organizational culture on the success of transformation strategies.